Current Trends and Challenges in Pharmacoeconomic Aspects of Nanocarriers as Drug Delivery Systems for Cancer Treatment - Milewska S (Dove Medical Press, 2021)
Sylwia Milewska,1 Katarzyna Niemirowicz-Laskowska,1 Gabriela Siemiaszko,2 Piotr Nowicki,1 Agnieszka Z Wilczewska,2 Halina Car1 1Department of Experimental Pharmacology, Medical University of Bialystok, Bialystok, 15-361, Poland; 2Faculty of Chemistry, University of Bialystok, Bialystok, 15-245, PolandCorrespondence: Katarzyna Niemirowicz-Laskowska; Halina CarDepartment of Experimental Pharmacology, Medical University of Bialystok, Szpitalna 37, Bialystok, 15-361, PolandTel +48602749149; +48604831512Email katarzyna.niemirowicz@umb.edu.pl; halina.car@umb.edu.plAbstract: Nanotherapy is a part of nanomedicine that involves nanoparticles as carriers to deliver drugs to target locations. This novel targeting approach has been found to resolve various problems, especially those associated with cancer treatment. In nanotherapy, the carrier plays a crucial role in handling many of the existing challenges, including drug protection before early-stage degradations of active substances, allowing them to reach targeted cells and overcome cell resistance mechanisms. The present review comprises the following sections: the first part presents the introduction of pharmacoeconomics as a branch of healthcare economics, the second part covers various beneficial aspects of the use of nanocarriers for in vitro, in vivo, and pre- and clinical studies, as well as discussion on drug resistance problem and present solutions to overcome it. In the third part, progress in drug manufacturing and optimization of the process of nanoparticle synthesis were discussed. Finally, pharmacokinetic and toxicological properties of nanoformulations due to up-to-date studies were summarized. In this review, the most recent developments in the field of nanotechnology’s economic impact, particularly beneficial applications in medicine were presented. Primarily focus on cancer treatment, but also discussion on other fields of application, which are strongly associated with cancer epidemiology and treatment, was made. In addition, the current limitations of nanomedicine and its huge potential to improve and develop the health care system were presented.Keywords: nanotechnology, pharmacology, pharmacoeconomic analysis, pharmacoeconomics, nanomaterials synthesis, clinical trials